Contributions in Analytic and Algebraic Number Theory Festschrift for S. J. Patterson - Blomer, Valentin; Mihăilescu, Preda (Springer Proceedings in Mathematics, 2012)
Contributions in Analytic and Algebraic Number Theory: Festschrift for S. J. Patterson is a collection of surveys and original work from experts in the fields of algebraic number theory, analytic number theory, harmonic analysis, and hyperbolic geometry. A portion of the collected contributions were developed from lectures presented at the "Patterson 60++ International Conference on the Occasion of the 60th Birthday of Samuel J. Patterson," held at the University of Göttingen, July 27-29, 2009. Many of the included chapters were contributed by invited participants.   This volume presents and investigates the most recent developments in various key topics in analytic number theory and several related areas of mathematics. It is intended for graduate students and researchers of number theory as well as applied mathematicians interested in this broad field.